WIZERUNEK HUMANISTY W WERBALIZACJACH STUDENTÓW WYDZIAŁU HUMANISTYCZNEGO UMCS W LUBLINIE - Karwatowska, Małgorzata; Litwiński , Robert (Studia Europaea Gnesnensia, 2018)
The intention of the authors is to attempt a recreation of the self-stereotype of a humanities person, by analyzing answers to the following questions/issues: 1) Who is a humanities person? 2) Name occupations in which such a person may be professionally involved. 3) List competences that are typical of a humanities person. 4) What distinguishes a person with a background in humanities from persons educated in different area? 5) Are such persons needed today?